What We Talk About When We Talk About Virtual Learning Environments - Flavin, Michael; Bhandari, Aditi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2021)
This is a literature review analysing articles published on virtual learning environments (VLEs), otherwise known as learning management systems, in higher education in the years 2014–2018. The Web of Science database was used to identity relevant articles over this five-year period. The sample comprises 99 peer-reviewed, academic journal articles. A coding sheet is used to analyse each article, identifying the research method, the classification of research (macro, meso, or micro), the focus of research (students, instructors, or both), and, where applicable, the specific brand of VLE. Most output on VLEs is found to be quantitative, to focus on students and on the micro level of learning and teaching, to not have a clear theoretical focus, to not specify which brand of VLE is used, and to be produced in affluent countries. This article adds to the understanding of VLE research by identifying the most frequent foci of research on VLEs, as well as identifying areas that have been under-researched.